SHOUSHTAR NEW TOWN: A SAMPLE OF SUSTAINABILITY IN IRANIAN CONTEMPORARY ARCHITECTURE - Jalilian, Mojir (MATTER: International Journal of Science and Technology, 2015)
Sustainable architecture could be defined as the creation of buildings for which only renewable resources are consumed throughout the process of design, construction and operation .there are different aspects which could be considerable in sustainability such as environmental and social factors. It could be said that the first traceable concepts of sustainability in Iranian contemporary architecture are visible in some buildings in 1960’s , whereas a couple of young architects would try to find solutions for climatic and social issues and moving toward a sustainable architecture. (Iran is one of the unique countries which have the widest variety of climates and ethnic groups, hence architectural solutions differ from one region to another in this country).In this paper, the architecture of Shoushtar new town, which is an example of avant-garde contemporary architecture in Iran, is studied according to its caring about climatic and social factors and the amount of success it has had in creating sustainable architecture .the research is qualitative which examines in-depth analysis on the case study (Shoushtar new town ) to better understand different aspects of the architecture.